1994
DOI: 10.1007/bf00010151
|View full text |Cite
|
Sign up to set email alerts
|

Mineralization of labeled N from cowpea [Vigna unguiculata (L.) Walp.] plant parts at two growth stages in sandy soil

Abstract: Cowpea [Vigna unguiculata (L). Walp.] has great potential as green manure due to its rapid N accumulation and efficient N 2 fixation. The objective of this study was to measure the rate of N mineralization from cowpea plant parts harvested at onset of flowering (5 weeks) and mid pod-fill (7 weeks) under near optimum conditions. Cowpeas were grown in a greenhouse and supplied with ~SNH415NO3 to isotopically label tissue. Cowpea leaves, stems, and roots were incorporated into a sandy soil (Psammentic Paleustalf)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 22 publications
2
8
0
1
Order By: Relevance
“…The main factor explaining net N mineralization (in % of added-N, positive or negative) was the residue-N content and its organic C:N ratio (R). Numerous authors have found significant relationships between N mineralization of catch crop and green manure residues and their N contents (Franzluebbers et al 1994;ThorupKristensen 1994;Wivstad 1999) or their C:N ratio (Franzluebbers et al 1994;Quemada and Cabrera 1995;Clement et al 1998;Jensen et al 2005). No relationship was found between N mineralization and biochemical characteristics (contents in parietal compounds and polyphenols), which confirms the findings of Thorup-Kristensen (1994) and Clement et al (1998).…”
Section: Discussionsupporting
confidence: 85%
“…The main factor explaining net N mineralization (in % of added-N, positive or negative) was the residue-N content and its organic C:N ratio (R). Numerous authors have found significant relationships between N mineralization of catch crop and green manure residues and their N contents (Franzluebbers et al 1994;ThorupKristensen 1994;Wivstad 1999) or their C:N ratio (Franzluebbers et al 1994;Quemada and Cabrera 1995;Clement et al 1998;Jensen et al 2005). No relationship was found between N mineralization and biochemical characteristics (contents in parietal compounds and polyphenols), which confirms the findings of Thorup-Kristensen (1994) and Clement et al (1998).…”
Section: Discussionsupporting
confidence: 85%
“…High rates of biomass and N accumulation have been observed previously at similar temperatures, where shoot biomass doubled over two weeks in cowpea (Franzluebbers et al, 1994). Mowing greatly reduced biomass, though there was moderate vegetative regrowth in the mowed treatment (Figure 1).…”
Section: Cover Crop Biomass and Nsupporting
confidence: 59%
“…The relationship between the C:N ratio or % N of plant residue and N min has been demonstrated in many studies but there is no consensus on the critical levels which result in either net N min or immobilization. Many soil science textbooks and technical agricultural publications suggest that residues with C:N ratios of <20-25:1 will result in net N min (Paul 2007;Sarrantonio 1994;Tisdale and Nelson 1975) yet a wider range from 20-40:1, has been documented to result in N min in both field and lab studies (Alexander 1977;Franzluebbers et al 1994;Iritani and Arnold 1959;Justes et al 2009;Vigil and Kissel 1991). Furthermore, soils managed under organic farming systems have been found to have greater organic carbon content, greater total soil N, and a more gradual release of inorganic N compared to their conventionally managed counterparts (Birkhofer et al 2008;Burger and Jackson 2003;Flieβbach et al 2007).…”
Section: Introductionmentioning
confidence: 97%